Manajemen Adaptif Wisata Pendakian di Jalur Thekelan, Gunung Merbabu Pasca Kebakaran Hutan - Aurilia Triani Aryaningtyas; Suwarti Suwarti; Lilis Suciyati (Gemawisata: Jurnal Ilmiah Pariwisata, 2026)
The forest fire that occurred in Mount Merbabu National Park in October 2023 had a significant impact on hiking tourism activities along the Thekelan trail in Semarang Regency, Central Java, Indonesia. This study aims to identify the impacts of forest fires on hiking tourism, explore stakeholders’ perceptions of post-fire management challenges, and develop an applicable adaptive management framework for the sustainable management of hiking tourism. The research employed a qualitative descriptive approach, with data collected through semi-structured interviews involving basecamp managers, national park officers, hikers, and local community members. The findings reveal that the wildfire caused severe vegetation damage, an estimated eighty percent decline in community income, and disruptions to both ecological balance and tourism activities. Despite these challenges, the local community demonstrated strong solidarity and active participation in recovery and rehabilitation efforts. The study proposes an adaptive management framework encompassing impact assessment, collaborative planning, rehabilitation and education, phased reopening, and continuous monitoring and adjustment. The adaptive management approach proves effective in enhancing the resilience of nature-based tourism destinations to future environmental disturbances and in promoting sustainable tourism practices.